Studi Komparasi : Perbandingan Penghitungan Pph 21 Sebelum Dan Sesudah Penerapan Tarif Pph 21 Terbaru Pada PT. UMS - Arief, Deysa Rosiana; Mardiani, Isni; Zuhdi, Amin; Pahala, Indra; Wahono, Puji (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Changes to the Income Tax (PPh) 21 rate scheme in 2024 have become a highlight in the context of tax policy in Indonesia. In order to understand the impact of these changes, this research aims to analyze and compare their effects on Information Technology (IT) companies. Quantitative research methods were used with a longitudinal research design involving data collection before and after the PPh 21 rate adjustment. As an independent variable, the PPh 21 rate scheme (old rate vs. new rate) was analyzed against dependent variables such as the amount of employee income and the amount of tax withheld. chosen as the research subject. Data collected from PT. UMS is a company operating in the information and technology sector. Comparative studies are used to compare data before and after rate changes. Research findings indicate that changes in PPh 21 rates have a significant impact on the amount of tax withheld at PT. UMS. The research results show that changes to the PPh 21 tariff scheme have a significant impact on the amount of tax withheld from the income of PT employees. UMS, indicates the need for IT companies to re-evaluate their tax strategies and pay attention to employee welfare. These findings also highlight the importance of tax compliance and openness to policy changes in maintaining the continuity of IT company operations amidst evolving tax dynamics. The implications of this research provide guidance for PT. UMS and similar companies in managing the impact of changes in PPh 21 rates effectively and ensuring proper compliance with applicable tax regulations. Keywords: income tax, tax management, comparative study